2023
DOI: 10.3390/socsci12110621
|View full text |Cite
|
Sign up to set email alerts
|

What Do Pupils Learn from Voting Advice Applications in Civic Education Classes? Effects of a Digital Intervention Using Voting Advice Applications on Students’ Political Dispositions

Thomas Waldvogel,
Monika Oberle,
Johanna Leunig

Abstract: To what extent does the use of Voting Advice Applications in (digital) civic education classes at school impact students’ political knowledge, attitudes, motivations and behavioral dispositions toward elections? This article provides answers to this question by presenting a sample analysis of the responses of 1189 pupils who participated in a digital civic education intervention, with the German Voting Advice Application Wahl-O-Mat at its core, whose usage was embedded in an elaborated didactical concept in ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Until very recently the evaluation of whether VAAs help citizens acquire political information beyond the "political match" output was viewed as a byproduct of VAA usage rather than the main goal. For instance, Schultze (2014) found that using Wahl-O-Mat in Germany enhanced political knowledge of party positions on political issues, whereas in another intervention where Wahl-O-Mat was embedded in civic education classes Waldvogel et al (2023) found a significant increase in young people's political efficacy and specific interest in the election campaign. Furthermore, Brenneis and Mauve (2021) explored the use of statements that presented specific arguments alongside the typical policy positions in a VAA.…”
Section: Improving the Understanding Of Statements In Vaasmentioning
confidence: 99%
“…Until very recently the evaluation of whether VAAs help citizens acquire political information beyond the "political match" output was viewed as a byproduct of VAA usage rather than the main goal. For instance, Schultze (2014) found that using Wahl-O-Mat in Germany enhanced political knowledge of party positions on political issues, whereas in another intervention where Wahl-O-Mat was embedded in civic education classes Waldvogel et al (2023) found a significant increase in young people's political efficacy and specific interest in the election campaign. Furthermore, Brenneis and Mauve (2021) explored the use of statements that presented specific arguments alongside the typical policy positions in a VAA.…”
Section: Improving the Understanding Of Statements In Vaasmentioning
confidence: 99%